It Takes Two to Tango: Coupling of Angiogenesis and Osteogenesis for Bone Regeneration - Grosso, Andrea; Burger, Maximilian G.; Lunger, Alexander; Schaefer, Dirk J.; Banfi, Andrea; Di Maggio, Nunzia (Frontiers in bioengineering and biotechnology, 2017)
Bone regeneration is a complex process requiring highly orchestrated interactions between different cells and signals to form new mineralized tissue. Blood vessels serve as a structural template, around which bone development takes place, and also bring together the key elements for bone homeostasis into the osteogenic microenvironment, including minerals, growth factors and osteogenic progenitor cells. Vascular endothelial growth factor (VEGF) is the master regulator of vascular growth and it is required for effective coupling of angiogenesis and osteogenesis during both skeletal development and postnatal bone repair. Here, we will review the current state of knowledge on the molecular cross-talk between angiogenesis and osteogenesis. In particular, we will focus on the role of VEGF in coupling these two processes and how VEGF dose can control the outcome, addressing in particular: (1) the direct influence of VEGF on osteogenic differentiation of mesenchymal progenitors; (2) the angiocrine functions of endothelium to regulate osteoprogenitors; (3) the role of immune cells, e.g., myeloid cells and osteoclast precursors, recruited by VEGF to the osteogenic microenvironment. Finally, we will discuss emerging strategies, based on the current biological understanding, to ensure rapid vascularization and efficient bone formation in regenerative medicine.